A comparative study of the effects of palm olein, cocoa butter and extra virgin olive oil on lipid profile, including low-density lipoprotein subfractions in young healthy Chinese people. (3rd April 2019) - Cheng, Chen; Wang, Di; Xia, Hui; Wang, Feng; Yang, Xian; Pan, Da; Wang, Shaokang; Yang, Ligang; Lu, Huixia; Shu, Guofang; He, Yaqiong; Xie, Yulan; et al.
Abstract: The aim of this study is to investigate the effects of palm olein (POL), cocoa butter (CB) and extra virgin olive oil (EVOO) on the lipid profile and low-density lipoprotein subfractions in a young, healthy Chinese population. After screening, 72 subjects were randomly assigned to three groups, and an 18-week randomized crossover trial was conducted. The first phase was a 2-week run-in period, followed by three phases of the 4-week experimental periods with a 2-week washout period between experimental periods. Three groups of subjects alternately consumed a Chinese diet enriched with the different test oils. The various indices of subjects were collected before and after each experimental period. Sixty-seven subjects completed the study, and there were no significant differences in conventional indices amongst the three groups at the beginning of the three experimental periods ( p  > .05). Each test oil accounted for approximately 40% of total fat intake and approximately 11.3% of the total energy supply. After controlling for dietary interventions, only the serum triglyceride level of the POL-Diet was significantly lower than that of the EVOO-Diet ( p  = .034), and most indices did not significantly differ amongst the three test oil diets ( p  > .05). POL, CB and EVOO have almost identical effects on serum lipids.